2021
DOI: 10.1016/j.celrep.2021.109645
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback by NUR77/Nr4a1 restrains B cell clonal dominance during early T-dependent immune responses

Abstract: Brooks et al. define a new role for NUR77in regulating clonal B cell competition during early humoral immune responses to immunization. The authors reveal that NUR77 is dispensable for germinal center size, but it serves to curb immunodominance when B cells must compete against each other into a limited niche.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…However, we were unable to identify an advantage for Nr4a1 -/mice in mounting responses to T-dependent immunogens like NP-KLH either in terms of GC size, antibody titer, or affinity maturation. 13,14 We instead found that the NR4A family regulates B cell responses specifically in competitive settings when T cell help is limiting, and this advantage was eliminated by excess T cell help (Figure 3B,C). 13 Since NR4A expression is induced in proportion to the strength of Ag stimulation, negative regulation by the NR4A family should also scale with Ag stimulation.…”
Section: While Icam1 and 2 Promote Formation Of T-b Conjugates Duringmentioning
confidence: 89%
See 3 more Smart Citations
“…However, we were unable to identify an advantage for Nr4a1 -/mice in mounting responses to T-dependent immunogens like NP-KLH either in terms of GC size, antibody titer, or affinity maturation. 13,14 We instead found that the NR4A family regulates B cell responses specifically in competitive settings when T cell help is limiting, and this advantage was eliminated by excess T cell help (Figure 3B,C). 13 Since NR4A expression is induced in proportion to the strength of Ag stimulation, negative regulation by the NR4A family should also scale with Ag stimulation.…”
Section: While Icam1 and 2 Promote Formation Of T-b Conjugates Duringmentioning
confidence: 89%
“…This would limit immunodominance of high‐affinity clones and permit greater expansion of lower affinity clones. To test this hypothesis, we sought to create a novel set of immunogens that would titrate relative immunodominance between a pair of competing B cell specificities by varying the conjugation ratio of NP to OVA protein 14 . In Nr4a1 –/– mice (and to a lesser extent in mb1‐cre Nr4a1 fl/fl mice), immunodominant B cell clones outcompete subdominant clones to a greater extent than in WT mice, regardless of the clonal hierarchy imposed by a given immunogen 14 .…”
Section: Roles Of Nr4a Family In B Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbubbles have been used for many applications, including cell isolations—more commonly known as Buoyancy Activated Cell Sorting (Akadeum Life Sciences, 2020; McNaughton et al, 2018; Jeon, D. & McNeel, D., 2022; Brooks et al, 2021), dead cell removal (Akadeum Life Sciences, 2022; McNaughton et al, 2018), cell therapy (Snow et al, 2022) and nucleic acid extractions from saliva (Akadeum Life Sciences, 2021). As detailed above, we have demonstrated a new protocol and application for microbubbles: viral nucleic acid extraction from wastewater using microbubbles.…”
Section: Discussionmentioning
confidence: 99%